Report on Staffing and Salaries, Fall 1988. Report Number 89-2 - California Community Colleges, Sacramento. Office of the Chancellor; California Community Colleges, Sacramento. Office of the Chancellor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This report presents fall 1989 demographic, staffing, salary, and workload information on all California community college employees, based on data from 69 of the 71 districts in the state. First, tables present the total number of district employees by primary occupational activity; full-time equivalency; type of assignment; weekly faculty contact hours by certificated staff; and a seven-year profile of full-time faculty and average salary paid. Next, tables are presented for each of six major categories of community college employees: contract and regular (full-time) faculty; temporary (part-time) faculty; full-time nonteaching professionals; full-time certificated administrators; full-time classified administrators; and all other full-time classified employees. For each group, tables provide data on percentage distributions by age, gender, ethnicity, employment classification, employment status, duration of employment contract/agreement, annual salary per schedule plus stipends, salary changes during the previous year, expenditures for mandatory contributions and district paid employee benefits, and overload salaries. Appendixes include district contract/regular faculty salary schedules. (JMC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrators; College Faculty; Community Colleges; Compensation (Remuneration); Employment Patterns; Faculty College Relationship; Faculty Workload; Full Time Faculty; Part Time Faculty; Personnel Data; Salaries; School Demography; School District Spending; School Personnel; Staff Utilization; State Surveys; Tables (Data); Two Year Colleges; California; Reports, Research; Numerical/Quantitative Data; Tests/Questionnaires.